Preserving and Promoting the Sindhi Ralli Quilts: A Case Study of Pakistan’s Artistry - Rauf, Anum; Kamal, Asma (Journal of Design and Textiles, 2023)
Sindh, the southern province of Pakistan, covers the lower Indus Valley that has a rich heritage of cultural crafts and traditions, proved by the excavations of Amri, Mehrgarh, Kot Diji, Mohenjo Daro, Chanhun-jo-daro, Kahu-jo-Daro, Brahmanabad, and Bhambore. This reflects centuries of occupation, migration, trade, and political influence among others. Artisans belonging to this area have been practicing these crafts generationally, due to which these crafts became a reason for the living Sindhi cultural heritage Among these many crafts, Ralli Work, which is unique because of its technique, patterns, and colors and is famous for its intricate artistry and work. Sindhi Ralli has its recognition when it is compared with other regions of the world because of its color combinations and geometrical design. Therefore, this research aims to highlight the fact that this age-old tradition should not only be preserved as part of our heritage but must be promoted wisely that can change the economic condition of the rural population. Although after 2003, many exhibitions and quilt festivals were organized by Western scholars in their own countries and within Pakistan but soon the promotions ended. For this purpose, Sindh has been selected and visited to explore the various Rallis and their making process in Pakistan. Besides this Sindh Museum, craft companies have been visited to check the current status of Ralli’s promotion in Pakistan. This study suggested that the government plays an active role in the proper patronization of this craft at the national and international levels and allocate funds and grants for the upcoming scholars and textile crafts researchers for the future excellence and to promote Ralli industry.